2005
DOI: 10.1080/01690960444000197
|View full text |Cite
|
Sign up to set email alerts
|

Masked cross-modal morphological priming: Unravelling morpho-orthographic and morpho-semantic influences in early word recognition

Abstract: 2005) Masked cross-modal morphological priming: Unravelling morpho-orthographic and morpho-semantic influences in early word recognition, Language and Cognitive Processes, 20:1-2, 75-114,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
164
4
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(182 citation statements)
references
References 26 publications
(56 reference statements)
13
164
4
1
Order By: Relevance
“…It is thought that the decomposition of the morphological structure would enable, and thus speed up, processing while reading (Elbro 1989). Support for this has been provided by several priming studies that have suggested the lexicon be morphologically organized (Diependaele, Sandra, & Grainger, 2005;Feldman, 1991;Leikin & Zur Hagit, 2006). In addition to aiding lexical processing, such segmentation assists in the pronunciation of letter sequences.…”
Section: Morphological Awarenessmentioning
confidence: 76%
“…It is thought that the decomposition of the morphological structure would enable, and thus speed up, processing while reading (Elbro 1989). Support for this has been provided by several priming studies that have suggested the lexicon be morphologically organized (Diependaele, Sandra, & Grainger, 2005;Feldman, 1991;Leikin & Zur Hagit, 2006). In addition to aiding lexical processing, such segmentation assists in the pronunciation of letter sequences.…”
Section: Morphological Awarenessmentioning
confidence: 76%
“…At the present stage of our knowledge, we cannot exclude that the compound frequency effect is also indicative of facilitation from semantic processing, given that semantic effects have been observed for very short initial time spans (cf., e.g., Diependaele, Grainger & Sandra, 2005;Hauk & Pulvermüller, 2004;Penolazzi et al, 2007;cf., also Baayen, Feldman & Schreuder, 2006, for evidence concerning a strong semantic component to the word frequency effect).…”
Section: Discussionmentioning
confidence: 99%
“…Sublexical models hold that complex words undergo obligatory parsing and that lexical access proceeds via their morphemes (cf., Taft, 1991;Taft & Forster, 1975, 1976. Supralexical models, by contrast, argue that morphemes are accessed only after the compound as a whole has been recognized (e.g., Diependaele, Sandra & Grainger, 2005;Giraudo & Grainger, 2001). Dual route models hypothesize that full-form based processing goes hand in hand with decompositional processing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The faster route 'wins' and gets to operate the processing of each particular word. Dual-route parallel models (such as Schreuder and Baayen (1995), Baayen and Schreuder (1999;) and models that combine morpho-orthographic and morphosemantic systems that may lead to either the whole-word or decomposition (proposed by Diependaele et al (2005)) respond to scientific evidence that many factors influence access to complex words (cf. Kuperman et al (2010) for a review of the area).…”
Section: Processing Of Morphological Complex Wordsmentioning
confidence: 99%